EML4–ALK fusion transcript is not found in gastrointestinal and breast cancers - Fukuyoshi, Y (Nature Publishing Group, 2008)
Fusion genes have been identified as chromosomal rearrangements in certain cancers, such as leukaemia, lymphoma, and sarcoma. The EML4–ALK (EML4: echinoderm microtubule-associated-protein-like 4; ALK: anaplastic lymphoma kinase) fusion gene has been identified as an oncogene in non-small-cell lung cancer (NSCLC). This study examined the presence of this fusion transcript in gastrointestinal and breast cancers. We evaluated the expression of the EML4–ALK transcript in 104 lung cancer cases and in 645 gastrointestinal and breast cancer samples. Only one of the lung cancer samples tested positive for the EML4–ALK fusion transcript, whereas none were detected in 555 gastrointestinal and 90 breast cancer cases. Our data suggest that the EML4–ALK fusion transcript is not present in gastrointestinal or breast cancers and is specific to NSCLC.